You can't make this stuff up ebook The complete guide to writing creative nonfiction — from memoir to literary journalism and everything in between. - Gutkind, Lee (2012)
From "the godfather behind creative nonfiction" ( Vanity Fair ) comes this indispensable how-to for nonfiction writers of all levels and genres, "reminiscent of Stephen King's fiction handbook On Writing " ( Kirkus ). Whether you're writing a rags-to-riches tell-all memoir or literary journalism, telling true stories well is hard work. In You Can't Make This Stuff Up , Lee Gutkind, the go-to expert for all things creative nonfiction, offers his unvarnished wisdom to help you craft the best writing possible. Frank, to-the-point, and always entertaining, Gutkind describes and illustrates every aspect of the genre. Invaluable tools and exercises illuminate key steps, from defining a concept and establishing a writing process to the final product. Offering new ways of understanding the genre, this practical guidebook will help you thoroughly expand and stylize your work.